Death, burial, and rebirth in the religions of antiquity - Davies, Jon, 1939- (Routledge, 1999)
Drawing on the sociological theory of Max Weber, this volume charts the significance of death to the emerging religious cults in the pre-Christian and early Christian world.
Keywords: Death -- Religious aspects -- History of doctrines.; Funeral rites and ceremonies, Ancient.; Future life -- History of doctrines.; Middle East -- Religion.; Rome -- Religion.; Death.; Funeral rites and ceremonies.; Middle East.; Medicine, Ancient.; Death; Funeral Rites; Religion -- history; Thanatology -- history; History, Ancient; Mediterranean Region; Middle East; Mort -- Aspect religieux -- Histoire des doctrines.; Funérailles -- Rites et cérémonies.; Vie future -- Histoire des doctrines.; Moyen-Orient -- Religion.; Funérailles -- Rites et cérémonies -- Histoire -- Jusqu'à 500.; Mort.; Moyen-Orient.; Médecine ancienne.; deaths.; funerals.; RELIGION -- Comparative Religion.; Funeral rites and ceremonies; Funeral rites and ceremonies, Ancient; Future life -- History of doctrines; Religion; Rome (Empire); Reïncarnatie.; Begrafenissen.; Riten.; Godsdiensten.; Oudheid.; RITOS FUNERÁRIOS -- ROMA ANTIGA.; RELIGIÃO ROMANA ARCAICA.; Religion romaine.; Rites et cérémonies funéraires antiques.; Electronic books.